Code-switching and screen translation in British and American films and their Italian dubbed version: a socio-linguistic and pragmatic perspective - Monti, Silvia (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2013)
Much attention has been recently focused on exploring how a language shapes its speakers’ identity in multiethnic contexts of interaction (Carter, 2004), where linguistic identities are constantly open to renegotiation, reconstruction and reinterpretation. From this perspective, multicultural audiovisual products prove to be one of the most apt media to represent the richness and complexity of real-life multilingual realities (Bleichenbacher, 2008) within which code-switching plays a crucial role. Starting from these assumptions, this paper sets out to investigate the conversational functions code-switching fulfils in two British and two American intercultural films: Bend it Like Beckham (Chadha, 2002), Ae Fond Kiss (Loach, 2004), Spanglish (Brooks, 2004) and Gran Torino (Eastwood, 2008), where it is functional both to plot development and to the bilingual immigrants’ characterisation (Wahl 2008). In establishing a specific socio-linguistic and pragmatic framing within which code-switching seems to operate in audiovisual products, the film scripts will be analysed: looking contrastively, in both the original and the Italian dubbed version, at the translation strategies of the different types of code-switching; focusing on the scenes where code-switching emphasizes the competing visions of the world held by the two generations (Myers-Scotton, 1993); pointing out which functions of code-switching are encoded in the Italian version and which ones are lost in translation; showing what can be achieved by both dubbing and subtitling in terms of transcultural transmission in conveying the “translaguaging space” (Wei, 2011, p. 1222) the immigrant characters live in.